COVID-19 control measures implemented by dentists in a northwestern municipality of São Paulo, Brazil - Lemos Silva, Renan; Moreno Carvalho, Monica; Estevam Simonato, Luciana (GMS Hygiene and Infection Control)
Introduction: The COVID-19 pandemic posed unprecedented challenges to public health, necessitating strict biosafety measures to mitigate virus transmission. In the dental field, professionals faced heightened risks due to direct contact with aerosols and bodily fluids during clinical procedures. This study aimed to analyze the control measures adopted in 2020 by dental surgeons in the municipality of Fernandópolis, located in northwestern São Paulo State, Brazil, focusing on the adequacy of biosafety practices in Basic Health Units (UBS). Results: The study found high adherence to the use of personal protective equipment, such as N95 masks, face shields, and disposable medical gowns, alongside rigorous hand-hygiene practices. However, initial difficulties in accessing supplies and raising patient awareness about preventive measures were reported. Conclusion: Although dental surgeons implemented effective measures to minimize contamination risks, continuous training and awareness strategies remain essential to enhance protection in dental settings.